Otitis externa by Pseudomonas aeruginosa associated with whirlpools. - Havelaar, A. H. (Cambridge University Press, 1983)
Over a period of about 1 year, otitis externa occurred in at least 300 visitors to a recreational park. The infections were associated with the presence of Pseudomonas aeruginosa in insufficiently chlorinated whirlpools.